ANALISIS NILAI PERCENTAGE DEPTH DOSE(PDD) TERHADAP VARIASI KEDALAMAN TARGET DAN LUAS LAPANGAN PENYINARAN MENGGUNAKAN PESAWAT LINAC-CX - Dian Milvita; Alimin Mahyudin; Vinny Alvionita (Universitas Riau, 2018)
Percentage Depth Dose (PDD) value measurement is done by varying the target depth and field size. The study was carried out with variations in target depth of 0 cm to 30 cm with 1 cm intervals and fields size ranging from (5x5) cm2 to (39x39) cm2 with intervals (2x2) cm2. PDD is a comparison of the radiation dose at a depth to the radiation dose at the maximum depth normalized by percentage. This study was also conducted to determine the value of radiation doses received by phantoms from the PDD measurement value. This research used 2 photon energy beam that is 6 MV and 10 MV. This study uses water phantom as a substitute for patients with radiation source technique Source Surface Distance (SSD). PDD measurements were performed using a chamber ionization detector. The results obtained showed that the number of radiation doses received by fantom increased to the maximum depth (zmax). After passing zmaks, the radiation dose received by the phantom has decreased. Likewise along with the increase in the amount of radiation field, the value of radiation doses received by phantoms will also increase.